Synthesis and Characterization of LiNiO2 Nanopowder with Various Chelating Agents. (10th May 2010) - Balandeh, Mehrdad; Asgari, Sirous
Abstract : LiNiO 2 powders were synthesized with acrylic acid, citric acid, oxalic acid, and triethanolamine (TEA) as a chelating agent. CrystallizedLiNiO 2 was synthesized in air at a calcinations temperature of 500 ∘ C for 12 hours, when the molar ratio of chelating agents to total metal ion (RPM) was 1.0. The TEA-assisted method had the highest intensity ratio of (003)/(104) peaks of X-ray diffraction (XRD) spectrum. The transmission electron microscopy (TEM) analysis indicates that the sample prepared with triethanolamine obtained the smallest particle size with average particle size of only 12 nm. The results indicate that chelating agents have an important role in the intensity ratio of (003)/(104) peaks of XRD spectrum, size and shape of powders.